Nanotribological Characterization of Lubricants between Smooth Iron Surfaces - Kasuya, Motohiro (Langmuir : the ACS journal of surfaces and colloids, 2017)
We performed the resonance shear measurement (RSM) for evaluating the nanorheological and tribological properties of model lubricants, hexadecane and poly(α-olefin) (PAO), confined between iron surfaces. The twin-path surface forces apparatus (SFA) was used for determining the distance between the surfaces. The obtained resonance curves for the confined lubricants showed that the viscosity of the confined hexadecane and PAO increased due to liquid structuring when the surface separation (D) decreased to a value less than 24 and 20 nm, respectively. It was also determined that the iron surfaces were lubricated by the hexadecane when normal load (L) was less than 1.1 mN, while the confined hexadecane behaved almost solid-like and showed poor lubricity when L was greater than 1.1 mN. In contrast, PAO between the iron surfaces showed high lubricity even under the high load (L > 2 mN). The surface separation of hexadecane and PAO at a hard wall contact between the iron surfaces was determined to be 4.6 ± 0.5 and 5.0 ± 0.4 nm by applying the fringes of equal chromatic order (FECO) for half-transparent iron films deposited on mica surfaces as substrates. We also characterized hexadecane and PAO confined between mica surfaces for studying the effect of substrates on the confined lubricants